The History of a Genuine Fake Philosophical Treatise (Ḥatatā Zar’a Yā‘eqob and Ḥatatā Walda Ḥeywat). Episode 2: The Time of Debunking, The Time in the Wilderness (from 1916 to the 1950s) - Anaïs Wion (Institut des Mondes Africains, 2021)
This second article in a series devoted to the history of the philosophical treatises attributed to Zar’a Yā‘eqob and his disciple Walda Ḥeywat explores the moment of “debunking”. How did doubts arise about the Hatatā Zar’a Yā‘eqob as early as 1916? How did its authorship come to be attributed to Giusto d’Urbino in 1920? After all, the article by the great philologist and historian C. Conti Rossini that turned this “rare jewel of Ethiopian literature” into a literary forgery is very succinct, and is more of a collection of pieces of evidence than an irrefutable proof. A few years later, another philologist, E. Mittwoch, tried to prove a Giusto d’Urbino authorship; however, his linguistic and philological analysis was flawed due to its reliance on an indirect source. Nonetheless, the academic community accepted these two scholars’ authoritative arguments. The present article follows up on this scholarly investigation in an effort to corroborate and enrich it, but also to show its shortcomings. Above all, it provides a new interpretation of the texts based on genetic criticism, and as such, tries to envisage the author, Giusto d’Urbino, at work on the Hatatā Zar’a Yā‘eqob. It also once again draws on Giusto d’Urbino’s unpublished correspondence with Antoine d’Abbadie with a view to better understanding the freethinker’s thought and motivations.